CHALLENGING BEHAVIORS ON INPATIENT MEDICAL UNITS: INTEGRATED, NON-PHARMACOLOGICAL APPROACH FOR PATIENTS WITH DEMENTIA. (16th November 2018) - Sutherland, E
Abstract: The San Francisco VA Health Care System (SFVAHCS) launched a taskforce to evaluate the needs of patients with complex medical and psychiatric needs that lead to extended hospital stays while focusing on improving quality of care, workplace safety, staff job satisfaction and decreasing length of stay/cost of hospitalization. Patients targeted for analysis were those with both dementia and behavioral challenges making placement outside of an acute hospital setting extremely difficult. Due to the outcomes the SFVAHCS initiated an innovative-best practice interdisciplinary mental health team to support patients, staff and families. The BEST Team (Behavioral Education and Support Team) is comprised of five team members and includes assessments, treatment planning, recommendations for care and patient/staff education. The BEST program collaborates with medical and surgical teams to offer education and assist with continuity of care of veterans with neurocognitive and behavioral challenges. The BEST also addresses length of stay, behavioral altercations, readmission, staff time off/turnover, staff satisfaction and feelings of safety, code greens, police standbys, and appropriate use of psychotropic meds when and if indicated. The BEST is an internationally-recognized, behavioral health team that is embedded within the acute inpatient medical environment to enhances quality of life, psychological well-being and behavioral function for our patients. BEST develops comprehensive treatment planning based on egalitarian interdisciplinary input while providing holistic, compassionate, and patient-centered health care.